2018
DOI: 10.1149/2.0971809jes
|View full text |Cite
|
Sign up to set email alerts
|

A Hydronium Solvate Ionic Liquid: Ligand Exchange Conduction Driven by Labile Solvation

Abstract: We observed a new class of proton conduction in a hydronium (H 3 O + ) solvate ionic liquid (IL). The IL is described as [H 3 O + · 18C6]Tf 2 N, composed of 18-crown-6-ether (18C6)-coordinated H 3 O + cation (solvate) and bis(trifluoromethylsulfonyl)amide (Tf 2 N -; Tf = CF 3 SO 2 ) anion. Self-diffusion coefficient measurements revealed that protons of H 3 O + (solute ion) move faster than 18C6 ligand (solvent), marking the first observation of ligand exchange conduction not only among solvate ILs but also am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…As reported previously, 8 in [H3O + •18C6]Tf2N, where unprotonated water is excluded and H3O + is solvated by 18C6 ligands, the chemical shift of the H3O + NMR signal is 10.85 ppm. As also discussed in our previous report, 21 one 1 H NMR singlet is observed at 8.18 ppm in an equimolar mixture of H2O and HTf2N (HTf2N•H2O), where its degree of dissociation is low and unprotonated H2O exists to some extent. Every H3O + signal in the compounds of this study is comparable to that of [H3O + •18C6]Tf2N.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…As reported previously, 8 in [H3O + •18C6]Tf2N, where unprotonated water is excluded and H3O + is solvated by 18C6 ligands, the chemical shift of the H3O + NMR signal is 10.85 ppm. As also discussed in our previous report, 21 one 1 H NMR singlet is observed at 8.18 ppm in an equimolar mixture of H2O and HTf2N (HTf2N•H2O), where its degree of dissociation is low and unprotonated H2O exists to some extent. Every H3O + signal in the compounds of this study is comparable to that of [H3O + •18C6]Tf2N.…”
Section: Resultssupporting
confidence: 76%
“…Pulsed-field gradient spin echo nuclear magnetic resonance (PGSE-NMR) measurements revealed that protons of H3O + move faster than those of 18C6 ligands in [H3O + •18C6]Tf2N. 21 Among solvate ILs and protic ILs, [22][23][24][25] this was the first observation of ligand exchange conduction without free neutral molecules. Further, unlike common solvate ILs and protic ILs, this cooperative proton relay is suppressed and H3O + come to move as slow as 18C6 ligands when diluted using equimolar 18C6 solvent.…”
Section: Introductionmentioning
confidence: 98%
“…Depending on the interactions between the Lewis‐acidic AlCl 3 and Lewis‐basic EC, they undergo ionization (e. g., dissociation, solvation, and complexation) due to the neutralization of Lewis acids and bases . The ability of a compound to act as a Lewis acid depends on the electrophilicity of the metal centre and availability of its lowest unoccupied molecular orbital (LUMO).…”
Section: Figurementioning
confidence: 99%
“…A proton-hopping conduction mechanism has been reported for a hydronium solvate ionic liquid (SIL) composed of a 18crown-6-ether (18C6)-coordinated H 3 O + solvated cation and the bis(trifluoromethanesulfonyl)amide anion (TFSA). 21 Proton hopping between imidazole (hIm) and imidazolium was also reported to happen in imidazole-enriched [h 2 Im + ][TFSA] PIL. 22 is lower than the glass transition temperature T g .…”
Section: ■ Introductionmentioning
confidence: 99%